The 'banquet' motif on the funerary stelai from Demetrias - Stamatopoulou, M (Peeters Publishers, 2016)
This paper discusses tombstones bearing the banquet theme (Totenmahl) from Demetrias in Thessaly. Nearly all carried painted decoration, as was typical for the city, and date to the 3rd and 2nd centuries BC. The introduction presents the evidence concerning their number, discovery, state of preservation and publication. Following this, their typology, iconographical features and epitaphs are discussed. The imagery of the Demetrias tombstones is compared with the evidence from Thessaly and the Greek world. The iconography of the stelai, similar to their typology, is heavily dependent on Athenian models, with an added emphasis on a luxurious ambience. Contrary to what has been proposed in the past, the study of the imagery and onomastics of the stelai shows that that the banquet motif was neither a minority choice in the city, nor was it limited to foreigners and/or persons of lower status. Rather, it was employed without much variation for Greeks and foreigner inhabitants of the city, regardless of ethnicity. In the multi-cultural environment of this Hellenistic harbour city, the population, with the exception of soldiers, priests and perhaps some Phoenician merchants, chose to be commemorated in a similar manner, placing emphasis on the family and comfortable life. Heroic allusions are few, but this is explained by the relatively early date of the Demetrias tombstones.